Perspectives on innovative non-fertilizer applications of sewage sludge for mitigating environmental and health hazards - Elham H. Fini; Mohammadjavad Kazemi; Lily Poulikakos; Georgy Lazorenko; Vajiheh Akbarzade; Anthony Lamanna; Peter Lammers (Communications Engineering)
Abstract As waste production increases and resources become limited, sewage sludge presents a valuable resource with potential beyond traditional land use and incineration. This review emphasizes exploring innovative non-fertilizer applications of sewage sludges and advocates for viewing wastewater treatment plants as sources of valuable feedstock and carbon sequestration. Innovative uses include integrating sewage sludge into construction materials such as asphalt pavements, geopolymer, cementitious composites, and masonry blocks. These methods not only immobilize heavy metals and mitigate environmental hazards but also support carbon sequestration, contrasting with incineration and land application methods that release carbon into the atmosphere. The review also addresses emerging technologies like bio-adhesives, bio-binders for asphalt, hydrogels, bioplastics, and corrosion inhibitors. It highlights the recovery of valuable materials from sewage sludge, including phosphorus, oils, metals, cellulose, and polyhydroxyalkanoates as well as enzyme production. By focusing on these non-fertilizer applications, this review presents a compelling case for re-envisioning wastewater treatment plants as sources of valuable feedstock and carbon sequestration, supporting global efforts to manage waste effectively and enhance sustainability.